2006
DOI: 10.1111/j.1365-263x.2006.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel preparation method on in vitro marginal microleakage of a flowable composite used as pit and fissure sealant

Abstract: It can be concluded that no significant difference was noted between the two types of enamel preparation when etching was performed. Preparing and treating the enamel surface exclusively by Er:YAG laser resulted in the highest degree of leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 15 publications
5
40
1
1
Order By: Relevance
“…3b and 3d). Although this finding aligns with some of the previously mentioned studies 25,26) , it was not in accordance with the findings of Moshonov et al In our opinion, this distinction emerged as a result of higher pulse repetition rate and lower pulse energy. For this reason, the laser groups with a higher pulse repetition rate caused deeper craters and grooves on the enamel surface (Figs.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…3b and 3d). Although this finding aligns with some of the previously mentioned studies 25,26) , it was not in accordance with the findings of Moshonov et al In our opinion, this distinction emerged as a result of higher pulse repetition rate and lower pulse energy. For this reason, the laser groups with a higher pulse repetition rate caused deeper craters and grooves on the enamel surface (Figs.…”
Section: Discussioncontrasting
confidence: 51%
“…The findings revealed that, there was no difference between the Er:YAG laser with acid etching and conventional techniques. Moreover, fissures prepared with the Er:YAG laser alone showed the highest degree of microleakage 26) . In the present study, the higher microleakage was found in both Er:YAG laser groups used alone according to all other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed giomer-based fissure sealant material represents advantages of resinbased and glass-ionomer-based sealants. The use of flowable composites as fissure-sealant material was also Microleakage and penetration depth of different fissure sealant materials after cyclic thermo-mechanic and brushing simulation Hüseyin HATIRLI 1 , Bilal YASA 1 and Elif YASA suggested 9) . The preventive effect of pit and fissure sealing is mainly based on the ability of sealant materials to flow through pits and fissures and completely fill them without any gaps or air entrapments.…”
Section: Introductionmentioning
confidence: 99%
“…4) Therefore, alternative methods have been proposed for preparing fissures other than acid etching for sealant retention like air abrasion and laser. [5][6][7] In recent years, lasers has been suggested as a pretreatment method to roughen enamel. [6][7][8] The main advantages that have been ascribed to laser technology are the lack of vibration and pain during the prepara-…”
Section: Introductionmentioning
confidence: 99%